Exploring the Potential of Halal Tourism in a non-Muslim Destination: The case of Portugal - João Domingues; Sofia Almeida (International Journal of Religious Tourism and Pilgrimage, 2024)
Halal Tourism has emerged as one of the most rapidly growing and auspicious market segments within the tourism industry. The main goal of this study is to ascertain whether Portugal has the necessary capabilities to develop a sustainable and competitive halal tourism market and if it can attract Muslim travellers. This research applied a qualitative methodology based on in-depth interviews with representatives of businesses companies and institutions from various subsectors of the tourism industry. Moreover, a netnographic technique was applied to gather secondary information. The results reveal that despite Portugal having full potential and all the conditions to develop halal tourism sustainably and competitively, there are still significant challenges to surpass, mainly a lack of products and services for this market, a lack of awareness from tourism agents, and the difficulty of complying with halal certification, as some businesses are not able to comply with the requirements or are not able to adapt to certain scenarios, mainly in the hospitality field. This study takes into consideration the tourism sector as a whole and not individual business needs. The outcome of this study aids decision-makers in Portuguese businesses and institutions in developing strategies and policies to generate significant competitive advantage in a crowded tourism market. The results provide a boost for halal tourism and help Portugal to become more competitive as a tourist destination. This facilitates a boost in Halal Tourism and helps Portugal as a touristic destination to become more competitive. Concerning the value of this research, to our knowledge, there is no study in Portugal of this depth which makes such a great contribution to halal tourism literature.